Bitumen products alter bax, bcl-2 and cytokeratin expression: An in vivo study of chronically exposed road pavers - Loreto, Carla; Rapisarda, Veneranda; Carnazza, Maria Luisa; Musumeci, Giuseppe; D'Agata, Velia; Valentino, Matteo; Martinez, Giuseppe (Journal of cutaneous pathology, 2007)
Background:  The skin of road pavers is chronically exposed to bitumen fumes, a mixture of volatile compounds and particles, containing several carcinogenic and non‐carcinogenic polycyclic aromatic hydrocarbons. Bitumen fumes can alter cutaneous barrier integrity in various ways and induce skin diseases. The present study was devised to investigate the expression of apoptosis proteins (bax and bcl‐2) and the cytokeratin pattern in skin specimens from road paving workers exposed to bitumen fumes using immunohistochemical techniques. Methods:  Skin forearm punch biopsies from 16 occupationally exposed workers and an unexposed control group were processed for immunohistochemistry using a broad‐spectrum anti‐cytokeratin antibody and monoclonal antibodies for bax and bcl‐2 immunostaining. Urinary 1‐hydroxypyrene (1‐OHP) was also determined. Results:  Morphological specimen evaluation showed epidermal thinning of exposed skin and flattened dermal papillae. In sections from exposed subjects, grade 3 bax overexpression and cytokeratin immunoreaction was detected in all layers, while bcl‐2 expression was downregulated (grade 1) and confined to the basal layer. There was a significant difference in 1‐OHP values between road pavers and the control group (p < 0.05). Conclusion:  Overexpression of the cytokeratin pattern and bax and underexpression of bcl‐2 in chronically bitumen‐exposed skin suggest that bitumen fumes induce activation of apoptosis as a defense mechanism.